Editorial - Maya Sánchez, Mario (Boletín Geológico, 2022)
Boletín Geológico publishes the special issue 48 (Spl.1), 2021, on airborne geophysics with the following articles: Moyano et al. present in this data article the airborne magnetometry and gamma-ray spectrometry datasets that the Servicio Geológico Colombiano has made available. The information was acquired in 15 blocks that cover approximately 520 000 square kilometers of Colombian territory, representing more than 850 000 linear km of information. The data were collected along flight lines separated by 500 m or 1000 m, depending on the area, with sampling rates of 10 Hz (8 m) and 1 Hz (80 m) for the magnetometry and gamma-ray spectrometry data, respectively. Puentes et al. present a synthesis of the Map of Geophysical Anomalies of Colombia for mineral resources, MAGC 2020 version. This map compiles the geophysical information acquired, processed, and interpreted by the Servicio Geológico Colombiano since 2013. This information was collected via airborne platforms (aircrafts) using magnetometry and gamma spectrometry. This version covers approximately 547 960 km2 of the national territory in the Andean (North and Central), Eastern (Eastern Plains and Amazon) and Caribbean zones (Perijá mountain range). Lara et al. disclose two case studies about the interpretation of geological features using airborne geophysical information in the Serranía de San Lucas – Antioqueño Batholith and eastern Colombia areas. The variations observed in airborne magnetic and gamma spectrometric data are used mainly to support the differentiation of geological units, to delimitate structures and to define compositional/lithological changes. In this context, the goal of this study is to support geological mapping through airborne magnetometry and gamma spectrometry geophysical data. Boletín Geológico acknowledges the collaboration of the following reviewers and their commitment to the peer-review process involved in this special issue on airborne geophysics: Álvaro Vargas, Lithosphera Earth Sciences Ltda., Colombia Bill Morris, McMaster University, Canada Hernán Ugalde, Brock University, Canada Leda Sánchez Bettucci, Universidad de la República, Uruguay Marco Nieto, MPX Geophysics, Canada Richard Smith, Laurentian University, Canada Stefania Radice, Universidad Nacional de Río Cuarto, Argentina Stephen Reford, Paterson, Grant & Watson Limited, USA Mario Maya Editor mmaya@sgc.gov.co boletingeologico@sgc.gov.co